Screening of Bioactive Compounds of the Brown Algae Turbinaria ornata (Turner) J. Agardh, 1848 From The Coastal Waters of Aboru Village, Central Maluku Indonesia - Sinay, Hermalina; El-sheekh, Mostafa (Brawijaya University, 2023)
Turbinaria ornata belonging to brown algae is a leading community in the sea water ecosystems which is rich in nutrients and bioactive compounds. The bioactive compounds of T. ornata are useful for medicine, pharmaceutical, industries and for people in the coastal area especially in Maluku Province as an archipelagic province. This study provides information about the importance and beneficial value of T. ornata and determines the bioactive compounds of T. ornata from in coastal waters of Aboru Village Central Maluku Regency. Screening of bioactive compounds was conducted qualitatively consisting of phenolics, tannins, flavonoids, saponins, triterpenoids, steroids, alkaloids and anthocyanins.The result of this study showed that qualitative screening of bioactive compounds of brown algae T. ornata positive for tannins, saponins, alkaloids, steroids, phenolics, and flavonoids, while triterpenoids, quinones, and anthocyanins were negative. Based on this research, it can concluded that T. ornata contains some bioactive compounds including tannins, saponins, alkaloids, steorids, phenolics, and flavonoids.